527 Patient-Reported Treatment Outcomes in the Mayo Clinic REM Sleep Behavior Disorder Registry: Efficacy of Melatonin and Clonazepam. (3rd May 2021) - Grayson, Kammi; Gossard, Thomas; Teigen, Luke; Feemster, John; McCarter, Stuart; Timm, Paul; Sandness, David; Carvalho, Diego; Junna, Mithri; Lipford, Melissa; Olson, Eric; Tippmann-Peikert, Maja; et al.
Abstract: Introduction: REM sleep behavior disorder (RBD) is characterized by disruptive, violent dream enactment behaviors (DEB), necessitating symptomatic treatment to prevent injury and reduce DEB frequency and severity. Melatonin and clonazepam are regarded as RBD therapeutic mainstays, although outcomes data remains limited. We surveyed RBD patients to determine their outcomes following melatonin, clonazepam, and melatonin-clonazepam combination therapy. Methods: Mayo Clinic RBD Patient Registry participants received an electronic survey concerning treatment type(s) and dose(s), efficacy, and adverse effects. The primary outcome was treatment efficacy, determined by comparing DEB frequency/severity ratings on a visual analog scale (VAS). Adverse effects severity was assessed by Likert scales. We comparatively analyzed VAS before and after treatment and adverse effects between treatments using non-parametric statistical tests. Results: Sixty-eight of 109 patients responded (62.3%; 64 had analyzable data) with a mean age of 67.7 years. Fifty-seven (85%) were men, with mean RBD symptom duration of 13.9 years. Patients receiving each treatment were: melatonin=30, clonazepam=8, and combination=12; 14 received other or no treatment. Baseline VAS ratings were similar between groups. Only melatonin (p=0.003) and combination therapy (p=0.039) improved VAS ratings; clonazepam monotherapy did not improve VAS. Only melatonin monotherapy was reported to lower VAS compared to untreated patients (p=0.02). Optimally effective mean dosages were melatonin 9.95±5.06 mg and clonazepam 0.81±0.48 mg. Patient frequencies reporting one or more moderately-severe side effect(s) were similar between melatonin (15%), clonazepam (7%), and combination therapies (9%). Twenty-five (36.8%) patients had received only one medication trial, while 41.2% required more than one medication. Of these, 15 (22.1%) tried 2 and 13 (19.1%) tried 3 or more treatments. Conclusion: Melatonin therapy at an approximate mean 10 mg dosage improved patient-reported DEB frequency/severity on VAS, compared between both previous intraindividual baseline ratings and with untreated patients, while clonazepam monotherapy did not, without differential adverse effects. Clonazepam monotherapy data were limited. These data inform future prospective melatonin symptomatic therapy trials for RBD. Additionally, 41.2% required more than one RBD pharmacological treatment, suggesting a current therapeutic gap and unmet need for future development of biologically-informed, evidence-based symptomatic RBD therapeutics. Support (if any):